For the first 60 positive integers, a = 1, n = 60, l = 60.
Sn = n/2(a + l)
s = 60/2(1 + 60) = 30(61)
For the next 60 positive integer, a = 61, n = 60, l = 120
Sum = 60/2(61 + 120) = 30(61 + 120) = 30(61) + 30(120) = s + 3600
Sum of first 120 positive integers = s + s + 3600 = 2s + 3600
Answer:
it should be somewhere along the lines of 2.25
Step-by-step explanation:
If you're using the app, try seeing this answer through your browser: brainly.com/question/2774989________________
Find the multiplicative inverse of
![\mathsf{z=6+2i}](https://tex.z-dn.net/?f=%5Cmathsf%7Bz%3D6%2B2i%7D)
________
The inverse multiplicative of
![\mathsf{z=a+bi}](https://tex.z-dn.net/?f=%5Cmathsf%7Bz%3Da%2Bbi%7D)
is
![\mathsf{\dfrac{1}{z}}\\\\\\ =\mathsf{\dfrac{1}{a+bi}\qquad\quad(a\ne 0~~and~~b\ne 0)}\\\\\\ =\mathsf{\dfrac{1}{a+bi}\cdot \dfrac{a-bi}{a-bi}}\\\\\\ =\mathsf{\dfrac{1\cdot (a-bi)}{(a+bi)\cdot (a-bi)}}\\\\\\ =\mathsf{\dfrac{a-bi}{a^2-\,\diagup\hspace{-10}abi+\,\diagup\hspace{-10}abi-(bi)^2}}](https://tex.z-dn.net/?f=%5Cmathsf%7B%5Cdfrac%7B1%7D%7Bz%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B1%7D%7Ba%2Bbi%7D%5Cqquad%5Cquad%28a%5Cne%200~~and~~b%5Cne%200%29%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B1%7D%7Ba%2Bbi%7D%5Ccdot%20%5Cdfrac%7Ba-bi%7D%7Ba-bi%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B1%5Ccdot%20%28a-bi%29%7D%7B%28a%2Bbi%29%5Ccdot%20%28a-bi%29%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7Ba-bi%7D%7Ba%5E2-%5C%2C%5Cdiagup%5Chspace%7B-10%7Dabi%2B%5C%2C%5Cdiagup%5Chspace%7B-10%7Dabi-%28bi%29%5E2%7D%7D)
![=\mathsf{\dfrac{a-bi}{a^2-b^2\cdot i^2}}\\\\\\ =\mathsf{\dfrac{a-bi}{a^2-b^2\cdot (-1)}}\\\\\\ =\mathsf{\dfrac{a-bi}{a^2+b^2}}\\\\\\\\ \therefore~~\mathsf{\dfrac{1}{a+bi}=\dfrac{a}{a^2+b^2}-\dfrac{b}{a^2+b^2}\,i\qquad\quad\checkmark}](https://tex.z-dn.net/?f=%3D%5Cmathsf%7B%5Cdfrac%7Ba-bi%7D%7Ba%5E2-b%5E2%5Ccdot%20i%5E2%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7Ba-bi%7D%7Ba%5E2-b%5E2%5Ccdot%20%28-1%29%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7Ba-bi%7D%7Ba%5E2%2Bb%5E2%7D%7D%5C%5C%5C%5C%5C%5C%5C%5C%0A%5Ctherefore~~%5Cmathsf%7B%5Cdfrac%7B1%7D%7Ba%2Bbi%7D%3D%5Cdfrac%7Ba%7D%7Ba%5E2%2Bb%5E2%7D-%5Cdfrac%7Bb%7D%7Ba%5E2%2Bb%5E2%7D%5C%2Ci%5Cqquad%5Cquad%5Ccheckmark%7D)
________
For this question,
![\mathsf{z=6+2i}](https://tex.z-dn.net/?f=%5Cmathsf%7Bz%3D6%2B2i%7D)
So,
![\mathsf{\dfrac{1}{z}}\\\\\\ =\mathsf{\dfrac{1}{6+2i}}\\\\\\ =\mathsf{\dfrac{6}{6^2+2^2}-\dfrac{2}{6^2+2^2}\,i}\\\\\\ =\mathsf{\dfrac{6}{36+4}-\dfrac{2}{36+4}\,i}\\\\\\ =\mathsf{\dfrac{6}{40}-\dfrac{2}{40}\,i}](https://tex.z-dn.net/?f=%5Cmathsf%7B%5Cdfrac%7B1%7D%7Bz%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B1%7D%7B6%2B2i%7D%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B6%7D%7B6%5E2%2B2%5E2%7D-%5Cdfrac%7B2%7D%7B6%5E2%2B2%5E2%7D%5C%2Ci%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B6%7D%7B36%2B4%7D-%5Cdfrac%7B2%7D%7B36%2B4%7D%5C%2Ci%7D%5C%5C%5C%5C%5C%5C%0A%3D%5Cmathsf%7B%5Cdfrac%7B6%7D%7B40%7D-%5Cdfrac%7B2%7D%7B40%7D%5C%2Ci%7D)
![\therefore~~\mathsf{\dfrac{1}{z}=\dfrac{3}{20}-\dfrac{1}{20}\,i}\quad\longleftarrow\quad\textsf{this is the answer.}](https://tex.z-dn.net/?f=%5Ctherefore~~%5Cmathsf%7B%5Cdfrac%7B1%7D%7Bz%7D%3D%5Cdfrac%7B3%7D%7B20%7D-%5Cdfrac%7B1%7D%7B20%7D%5C%2Ci%7D%5Cquad%5Clongleftarrow%5Cquad%5Ctextsf%7Bthis%20is%20the%20answer.%7D)
I hope this helps. =)